Educa????o e emancipa????o no pensamento de Theodor A. Adorno e Edgar Morin. - Quintal, T??nia Maria Massaruto de (2011)
In the context in which the formative processes takes place, being the education at the mercy of the social environment determinations, it finds itself little vigorous to give to its contribution to the process of human emancipation. We believe that just as the education can fulfill the reproduction task, it can and it must fulfill its role in the transformation of the current way of production of the existence. We understand that the matter of Emancipation and Education still needs to be discussed through a theoretical debate that contemplates the quandaries and perspectives of the formation in the contemporaneity. In this sense, the object of the present research is the position of Theodor W. Adorno and of Edgar Morin regarding the possibility of human emancipation and the role of education in it, as well as the relation between both positions in terms of proximities and distances. Adorno, a thinker of the Critical Theory, produced important reflections concerning the possibilities and impediments of the formative processes in the capitalist society, denouncing the semiformation and the instrumental rationality that lead to the barbarity and alerting on the necessity of an education that enables an emancipatory rationality. Edgar Morin, a thinker of the Theory of the Complexity, worried about the dilemmas of the education in the contemporary world in which the knowledge is fragmented in disciplines, alerts us on the necessity of an education for the lucidity, in favor of an open rationality. Morin criticizes the gap between fragmented knowledge and the each time more multidimensional reality, identifying the discrepancy between both. The complex reality becomes invisible and leading man to servitude and hindering his freedom. The objective of this research was to identify and to present how each author understands the relation between Education and Emancipation considering the singularity and specificity of each and respecting the theories that they represent. This is a theoretical-bibliographical research that chose reading, analyzing, interpreting and discussing the work of these two authors, aiming to contribute for the Educational Theory in order to extend the understanding of the relations between education, society and emancipation.